A Comparison Study of the Thermal Fatigue Properties of Three Ni‐Based Cast Superalloys Cycled from 20 to 1100 °C. Issue 7 (22nd March 2019) - Zhou, Tongjin; Ding, Hongsheng; Ma, Xiuping; Feng, Wei; Zhao, Huibin; Li, Ailan; Meng, Yu; Zhang, Huaxia
Abstract : The thermal fatigue properties of cycling from 20 to 1100 °C, a new kind of Ni‐based cast superalloy, named N3 are studied and the results are compared with those of other alloys, namely, K4002 and K403, corresponding to simulation analysis. The results show that the cracking models of the three alloys are basically the same; that is, when the temperature is alternately changed, cracks are easily formed at the interface of the matrix and carbide due to differences in the thermal expansion coefficients of the matrix and carbide. The N3 alloy contains a block‐shaped ( γ + γ′ ) eutectic with a volume fraction of 15.5%, which effectively hinders crack propagation, thereby resulting in the best thermal fatigue performance among the investigated alloys. The K4002 alloy also has a sunflower‐like eutectic with a volume fraction of 12.5%, which also shows good structural stability and excellent thermal fatigue properties. However, the K403 alloy exhibits poor thermal fatigue performance for the transformation of the carbides during thermal fatigue; in this case, the carbides form chain‐like M23 C6 carbides at the grain boundaries or interdendritic area because of unstable intrinsic character of the alloy. The results also demonstrate that a low eutectic content with a small volume fraction (2.2%) of the K403 alloy does not hinder crack propagation. Abstract : The thermal fatigue properties of cycling from 20 to 1100 °C, a new kind of Ni‐based cast superalloy, named N3 are studied, and the results are compared with those of other alloys, corresponding to simulation analysis. The results show that the N3 alloy contains a block‐shaped ( γ + γ ′) eutectic with a volume fraction of 15.5%, which effectively hinders crack propagation.